Comparison of Continuous Percolation and Ultrasound-Assisted Extraction (UAE) Methods on Total Phenolic Content of 70% Ethanol Extract of Purslane (Portulaca oleracea L.) - Aditya Sindu Sakti; Fransisca Dita Mayangsari; Sri Bintang Sahara Mahaputra Kusuma Negara; Elasari Dwi Pratiwi; Sandrawati (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Portulaca oleracea L., commonly known as Krokot, is rich in phenolic compounds with notable pharmacological benefits. Optimizing extraction methods is critical to maximize its bioactive potential. Objective: This study aimed to compare the efficiency of Continuous Percolation (CP) and Ultrasound-Assisted Extraction (UAE) in obtaining total phenolic content (TPC) from 70% ethanol extract of P. oleracea. Methods: Dried powdered P. oleracea was subjected to CP and UAE using a 1:10 (w/v) plant-to-solvent ratio. Qualitative screening with FeCl₃ confirmed the presence of phenolics. TPC was quantified using the Folin–Ciocalteu method, expressed as mg gallic acid equivalent (GAE)/g extract. Statistical analysis included normality testing, Levene’s test, and the Mann–Whitney U test. Results: UAE yielded significantly higher TPC (420.04 ± 0.40 mg GAE/g) compared to CP (354.30 ± 0.00 mg GAE/g; p = 0.034), although CP produced a higher extract mass. Statistical results confirmed the superiority of UAE in selectively extracting phenolic constituents. Conclusion: UAE is more effective than CP in extracting phenolic compounds from P. oleracea, likely due to enhanced cavitation-induced mass transfer. This method is recommended for maximizing phenolic recovery in plant-based extractions, especially for thermolabile compounds.